문명전환의 시대와 글로벌 민주주의의 위기 - 그 의미와 세계시민교육에 주는 시사점 - 김윤철(Yun Cheol Kim) (교양교육연구, 2024)
이 논문은 문명전환의 시대와 글로벌 민주주의의 위기가 어떤 의미인지, 또 그것이 세계시민교육에 시사하는 바가 무엇인지를 향후 ‘논의의 방향성’ 설정의 차원에서 살펴본다. 이때 문명전환의 시대는 문명을 구성하는 핵심 요소인 주체, 가치, 체제의 재구성을 요구하나, 글로벌 민주주의의 위기는 문명전환의 실천인 정치와 그 주체인 시민의 죽음을 가져왔음을 논한다. 이에 따라 향후 세계시민교육은 가치중립적이고 정치성을 배제하는 교육모델의 정립과 기법의 개발에 치중하는 것을 넘어서야 한다고 주장한다. 그리고 이때 위기 인식을 공유하는 주체로서 세계시민교육 수행자들을 조명하고, 이들의 ‘변혁적 교육 실천론’에 대한 탐구에 기초한 교육 비전과 전략을 모색할 것을 제안한다. This paper examines what the era of civilizational transformation and the crisis of global democracy mean, and what it means for global citizenship education, from the perspective of setting the ‘direction of discussion’ in the future. At this time, it is argued that the era of civilizational transformation requires the reconstruction of the subject, value, and system, which are the core elements that constitute civilization, but the crisis of global democracy brought abouth the death of politics, which is the practice of civilization transformation, and the citizens who are its subjects. Accordingly, it is argued that future global citizenship education should go beyond focusing on the establishment of educational models and development of techniques that are value-neutral and exclude politics. And at this time, this paper propose to shed light on global citizenship education practitioners as subjects who share awareness of the crisis and seek educational visions and strategies based on exploration of their ‘transformative educational practice theory’. KCI Citation Count: 0